ATL: A model transformation tool - Jouault, Frédéric; Allilaire, Freddy; Bézivin, Jean; Kurtev, Ivan (Science of computer programming, 2008)
In the context of Model Driven Engineering, models are the main development artifacts and model transformations are among the most important operations applied to models. A number of specialized languages have been proposed, aimed at specifying model transformations. Apart from the software engineering properties of transformation languages, the availability of high quality tool support is also of key importance for the industrial adoption and ultimate success of MDE. In this paper we present ATL: a model transformation language and its execution environment based on the Eclipse framework. ATL tools provide support for the major tasks involved in using a language: editing, compiling, executing, and debugging.